Growth and yield models for Centrolobium ochroxylum Rose ex Rudd in silvopastoral systems of Ecuadorian western lowlands - Cañadas-López, Álvaro; Gamboa-Trujillo, Paul; Wehenkel, Christian (Frontiers in Forests and Global Change, 2025)
Centrolobium ochroxylum Rose ex Rudd, known as Amarillo Guayaquil (AG), is a tropical tree species found in secondary vegetation or the wild in the western lowland region of Ecuador (WLRE). AG has heavy (0.78 g/cm3) and durable wood, with whitish sapwood and orange-yellow heartwood, making it ideal for carpentry and construction. The International Union for Conservation of Nature in 2021 classified AG as a threatened and critically endangered tree species. However, information on the forest's growth and yield is limited. The primary objective of this study was to evaluate the first provisional models of growth, yield, site index (SI), volume, and diameter at breast height (DBH) - total height (H) relationships developed for AG planted in live fences in WLRE. A total of 415 sample plots, each measuring one ha in area, were surveyed. AG trees were arranged in live fences, and UTM coordinates and planting dates were recorded. H and DBH were measured in 160 trees per plot in 2004, 2009, 2012, 2016, and 2018. To model volume, diameters were measured at different heights on randomly selected trees in 195 study sites. Cross-validation revealed that the CR-GADA model, with its three parameters, achieved a better balance between fitness and generalisability than the CR-H model. The Spurr function was found to be the best model for determining the total volume. The linear model was selected to describe the H-DBH relationship in the study region because of its stability and statistical significance. However, the model of Larson showed better overall indicators of fit. Variation of the H-DBH relationship was observed according to the SI. The maximum MAI was 14.8 m3 ha−1 yr−1 at age 26 years on the best sites, whereas, on less favorable sites, the maximum MAI was 4.4 m3 ha−1 yr−1 at age 30 years. These models are preliminary and require validation with independent samples. Future studies should include data from mature plots and conduct economic analyses on silvopastoral systems, as well as study the carbon sequestration of AG to encourage reforestation.